Control of an active bus voltage limiter with modified space vector pulse width modulation strategies in regenerative applications. (February 2019) - Gao, Zhigang; Chen, Te; Zhang, Chao
Abstract: This paper proposes an active bus voltage limiter with a modified modulation strategy for bi-directional power flow applications. When the motor is braking, the regenerative energy raises the DC bus voltage. Additional shunt resistors are usually used to dissipate the regenerative energy, which is a waste. The active rectifiers, which are also mentioned as PWM (Pulse Width Modulation) rectifiers, can transfer the regenerative power to the power grid but the cost is high and not economic, especially when the regenerative power is comparatively low. This paper investigates the zero-sequence current produced by the active bus voltage limiter and then presents a modified space vector modulation strategy to effectively suppress the zero-sequence current and keep the unity power factor. The analysis about the control strategy of the topology is carried out. And the algorithms for regenerative applications are discussed. An industrial prototype is built to verify the configuration. Highlights: The proposed limiter can transfer the regenerative energy to the power grids. The model of the zero-sequence current generated in the applications is established. A modified SVPWM is proposed and the zero-sequence currents are suppressed. The strategy proposed can be further used when many inverters run in parallel. An industrial prototype is built and has been used in elevators.